The association between arterial stiffness and circulating adipokine in patients with type 2 diabetes and comorbid overweight or obesity - Sai Krishna Ragh Varahabhatla; Soloviuk, O. O.; Soloviuk, O.; Nazarenko, О.; Солов'юк, Олександр Олегович; Назаренко, Олена Валеріївна (My University, 2021)
Objective: Omentin-1 is a circulating adipokine with anti-infl ammatory, antiatherosclerotic, cardioprotective effects. It is hypothesised that reduced levels of omentin-1 is connected with increase in arterial stiffness, thus leading to the rise in acute vascular events. A strong relationship between arterial stiffness and the levels of circulating omentin-1 in patients with diabetes mellitus type 2 (DM-2) and comorbid overweight or obesity was adapted from literature which necessitated for this study.
Keywords: тези доповідей